2001
DOI: 10.1128/mcb.21.19.6495-6506.2001
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Activity Represses Gamma Interferon-Inducible HLA-DR Gene Expression following the Establishment of a DNase I-Hypersensitive Chromatin Conformation

Abstract: Expression of the retinoblastoma tumor suppressor protein (Rb) is required for gamma interferon (IFN-␥Major histocompatibility complex (MHC) class II molecules are heterodimeric cell surface glycoproteins comprised of both a heavy (alpha) chain and a light (beta) chain. MHC class II molecules (HLA-DR, -DP, and -DQ in humans) bind and display peptide antigens for recognition by CD4 ϩ T lymphocytes. Recognition of the MHC class II heterodimer-antigen complex by the T-cell receptor and the accessory protein CD4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 65 publications
4
67
0
Order By: Relevance
“…Results indicated that MS-275 facilitated substantial induction of cell surface HLA-DR, when compared to normal skin fibroblasts, a positive control for the normal level of the HLA-DR IFN-g response. This result is consistent with results obtained with other HDAC inhibitors 8) and indicates that an HDAC inhibitor suitable for patient therapy can facilitate surface HLA-DR induction.…”
Section: Methodssupporting
confidence: 82%
See 3 more Smart Citations
“…Results indicated that MS-275 facilitated substantial induction of cell surface HLA-DR, when compared to normal skin fibroblasts, a positive control for the normal level of the HLA-DR IFN-g response. This result is consistent with results obtained with other HDAC inhibitors 8) and indicates that an HDAC inhibitor suitable for patient therapy can facilitate surface HLA-DR induction.…”
Section: Methodssupporting
confidence: 82%
“…To further clarify the initial results, we determined whether the YY1 site, which tethers a YY1-HDAC complex to the HLA-DRA promoter, 8) was related to the MS-275 effect. We transfected an HLA-DRA promoter luciferase construct, termed pDRA, and pDRA lacking the YY1 site, termed pDRA YY1mut, into the H2009 cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible mechanism is that TSA alters the DNA-binding ability of Oct-1 or NF-Y. In fact, it has been reported that the binding activity of Oct-1 to the HLA-DRA promoter is greatly reduced by TSA treatment (Osborne et al, 2001). However, EMSAs showed that TSA treatment did not change the affinity of nuclear factors for the NF-Y or Oct sites in the murine GADD45g promoter (unpublished observations).…”
Section: Discussionmentioning
confidence: 96%